Karakterisasi Protease Ekstraseluler Clostridium spp. T11-3 - Loli Natalia; Lily Nathalia; Anja Meryandini (Universitas Atma Jaya Yogyakarta, 2006)
Protease is one of the leather commercial enzymes which is widely used such in food processing, medicine and leather industry. Clostridium sp T11-3 was isolated from Tiu Jeruk River in Nusa Tenggara Barat. Sequence analysis of 16S rRNA indicated that Clostridium spp T11-3 was closely related to C. bifermentans. This isolate produced maximum protease activity after 18 hours of cultivation in liquid media. Protease of Clostridium spp 11-3 displayed maximum activity at pH 5 and 60oC with casein as substrate. In the presence of 1 mM divalent ion Mg2+ the enzym activity increased to 141 %, while others ion divalent (Ca2+, Zn2+, Cu2+, Fe2+, and Co2+) inhibited protease activity.